LOW δ18O ECLOGITES FROM THE KOKCHETAV MASSIF, NORTHERN KAZAKHSTAN - Masago H.; Maruyama S.; Rumble D.; Ernst W.G.; Parkinson C.D. (My University, 2003)
Oxygen isotopic compositions of silicates in eclogites and whiteschists from the Kokchetav massif were analyzed by whole-grain CO2-laser fluorination methods. Systematic analyses yield extremely low δ18O for eclogites, as low as −3.9‰ for garnet; these values are comparable with those reported for the Dabie-Sulu UHP eclogites. Oxygen isotopic compositions are heterogeneous in samples of eclogite, even on an outcrop scale. Schists have rather uniform oxygen isotope values compared to eclogites, and low δ18O is not observed. Isotope thermometry indicates that both eclogites and schists achieved high-temperature isotopic equilibration at 500–800 °C. This implies that retrograde metamorphic recrystallization barely modified the peak-metamorphic oxygen isotopic signatures. A possible geological environment to account for the low-δ18O basaltic protolith is a continental rift, most likely subjected to the conditions of a cold climate. After the basalt interacted with low δ18O meteoric water, it was tectonically inserted into the surrounding sedimentary units prior to, or during subduction and UHP metamorphism.
Keywords: eclogite; Kokchetav massif; low d18O; whiteschist